Importancia de la actividad física en pacientes de la tercera edad que acuden a la casa del adulto mayor del IESS de Riobamba para mejorar la flexibilidad y la movilidad articular durante el periodo de marzo a agosto del 2011 - Vera Torres, Maritza Gabriela (2012)
Aging is a set of changes that the time factor is in the living being, is a cycle of the life of the human being and as such, always comes. Arrival leads to a series of losses in the functional capabilities that will not only be increased with the lack of physical activity, but that this (inactivity) operates in the same way as the ageing. There are some risk factors for diseases with age and inactivity: excessive food, high blood pressure, smoking and alcoholism, sedentary lifestyle, osteoporosis, obesity, stress, loneliness. Among the factors that retard aging are: continued physical activity, good nutrition, adequate sleep, social participation. You know, because that age produces structural changes, and a decrease in physiological functions. They have shown delays in this process of involution. On the bone side, there has been a more athletes than in sedentary bone density. With regard to the resistance the realization of a properly designed exercise program improves health and reduces the risk of heart disease. In general, considered that regular vigorous physical activity produces improvements in the individual at any age. Logically occur declines associated with aging, but despite this, sportsmen and women of advanced age may pay to a high level. Physical exercise also has a positive impact on psychological aspects. Sporting activities increase the sense of personal achievement, the feelings of competence and self-efficacy, increasing the social and psychological benefits that sport has the welfare of older persons. Improvement of mood, decreases depression and anxiety, and reduces the somatic symptoms. In addition, in the older with some kind of physical deterioration, sport increases the sense of control and well-being during the exercises. There are many studies on the effects of the practice of sports in older people. All of them pointed out that the practice of leisure-time physical activities in old age helps keep young body and spirit.